Establishing reference values and evaluation of an in-house ferric reducing antioxidant power (FRAP) colorimetric assay in microplates - Ustundag, Yasemin; Huysal, Kagan; Kahvecioglu, Serdar; Demirci, Hakan; Yavuz, Senol; Sambel, Murat; Unal, Dursun (The European Research Journal, 2016)
Objective. The total antioxidant capacity (TAC) of a sample can be measured with a ferric reducing antioxidant power (FRAP) assay. There are commercially available kits for FRAP assays, however they are more expensive than in-house kits. We aimed to evaluate a FRAP direct measurement method under our laboratory conditions using a microplate reader and establish reference values to use in future research projects. Methods. An in-house microplate adaptation of the FRAP method was evaluated. Reference values of FRAP were established for one hundred and twenty subjects aged between 25-55 years. FRAP levels were estimated in 30 serum samples with high glucose concentration, 44 hyperbiluribinemic neonatals and 16 patients receiving renal replacement therapy (RRT). Results. The mean FRAP level was 890±235 µmol/L. The median TAC level was 904 µmol/L. This method was found to be linear up to at least 2000 µmol/L. The intra- and inter-assay coefficients of variation were 2.7-6.7% and 5.3-10.1%, respectively. The mean FRAP level was lower than normal in diabetes and RRT patients and higher in hyperbiluribinemic neonatals (687±209 µmol/L, 609±250 µmol/L and 945±187 µmol/L, respectively). Conclusions. Our reference values give comparable results with the literature. This method is simple, reliable, and inexpensive. It could be used for studies of oxidative stress-related diseases.